2018
DOI: 10.7573/dic.212543
|View full text |Cite
|
Sign up to set email alerts
|

The biosimilars journey: current status and ongoing challenges

Abstract: Biosimilar products are already approved and marketed in several countries. The Food and Drug Administration has approved ten different biosimilars, and the European Medicines Agency has approved 40. Even though this scenario has provided important experience with biosimilar products, there are still challenges and unanswered questions. Up to now, a good amount of knowledge has been gathered in order to support the importance of the totality of evidence and the construction of a biosimilarity exercise for regu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 54 publications
0
6
0
Order By: Relevance
“…Therefore, it is imperative that these similarity studies are carried out in an appropriate population group. The most sensitive population group must be chosen in order to allow an accurate detection of clinically meaningful differences [ 26 ]. In the case of adalimumab, the best population were patients with either psoriasis or rheumatoid arthritis.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, it is imperative that these similarity studies are carried out in an appropriate population group. The most sensitive population group must be chosen in order to allow an accurate detection of clinically meaningful differences [ 26 ]. In the case of adalimumab, the best population were patients with either psoriasis or rheumatoid arthritis.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, despite this increasing trend of biotechnological drug use in rare diseases, information on the pharmacokinetics, pharmacodynamics, and pharmaceutical application of these drugs is still limited in children, especially in those with rare diseases, compared to small-molecule drugs [9]. Besides, the use of biotechnological drugs other than the indications for which they are licensed takes place through extrapolation [24]. Considering their use in rare diseases, it may be suggested that the existing risk management plans of these drugs may be more likely to accompany various uncertainties in rare disease-oriented practice and that additional challenges may arise, indicating the need for additional measures.…”
Section: Discussionmentioning
confidence: 99%
“…Extrapolation of Indications: This topic had been an important regulatory advantage for biosimilars and had a direct impact on costs to the health systems. It involves considering the potential to extrapolate the efficacy and safety data from one already studied condition to the other indications of the reference product, for which the biosimilar was not directly tested [14].…”
Section: Other Regulatory and Clinical Questions On Biosimilars: Extr...mentioning
confidence: 99%
“…It is well known that even different batches of the same reference product can exhibit minimal differences through time. These minimal changes could have a direct impact on pharmacokinetics (PK) and pharmacodynamics (PD), as well on efficacy and safety, so the similarity exercise must include a batch-to-batch evaluation of biosimilars in comparison with the reference product [14].…”
Section: Introductionmentioning
confidence: 99%